An embezzler test for norms, standards and regulations. Issue 3 (11th August 2021) - Cardao-Pito, Tiago
Abstract : Purpose: The purpose of this study is to address the question that economic standards, norms and regulations can possess weak spots that might be exploitable for the embezzlement of an organization's assets with resultant material consequences in money laundering, tax evasion, fraud, corruption and other potential financial crimes. Design/methodology/approach: The author's methodological approach is to introduce and discuss a new logical-deductive test that the author names "embezzler test". The author's test investigates regulatory architectures from the perspective of someone attempting to divert assets from or to an organization. It appraises whether a potential embezzler could divert resources without being detected and sanctioned. Findings: The embezzler test can be applied to a broad range of standards, norms and regulations. Research limitations/implications: This new test can be improved and further calibrated in future research. Practical implications: Researchers, regulators and law makers can use the new test to identify and eventually fix weak spots for embezzlement in norms, standards and regulations. Originality/value: To the best of the author's knowledge, such a test has never been formulated or applied before to identify weak spots for potential embezzlement in regulatory architectures.